PTH-030 Management of sporadic duodenal polyps and risk of colorectal carcinoma. (23rd September 2015) - Culver, E L; Green, L; Cullen, S; Gorard, D; McIntyre, A S
Abstract : Introduction: Duodenal polyps occur infrequently. Their natural history and association with colonic lesions is unclear, presenting diagnostic and therapeutic dilemmas. Methods: This single-centre retrospective observational study identified patients with sporadic duodenal polyps (SDP) from endoscopy, histology and case records over a 10-year period (1998–2008). Patients with polyposis syndromes, peri-ampullary or ampullary polyps were excluded. Results: SDP's were recorded in 69 patients (97 polyps) out of 21 516 endoscopies, prevalence 0.32%, median age 69 years (range 23–90), equal sex distribution (M/F 32:37). Most frequent indications for endoscopy in this group were dyspepsia (28.9%) and anaemia (20.3%). Polyps were usually solitary (76.7%), between 5 and 10 mm in size (53.4%) and found in the first part of the duodenum (56.5%). Biopsies were taken in 82.6% of cases, most frequently finding gastric metaplasia (26%). Adenomas were identified in five cases (7.2%) prevalence 0.02%, were solitary (71.4%), of variable size (3–15 mm) and found in all parts of the duodenum. There were no duodenal carcinomas. Treatment was with endoscopic removal by snare polypectomy or hot biopsy for adenomas and large polyps over 15 mm (10.1%). Frailty and co-morbidity contraindicated therapeutic procedures in some (7.2%). Repeat endoscopy revealed residual disease in two-thirds and recurrence in a third of cases, over a mean follow-up of 13.6 months (range 2–34), all successfully treated with argon plasma coagulation. One patient required blood transfusion for post-polypectomy bleeding. There were no other complications. Five patients died of unrelated causes during a median follow-up of 49 months (range 1–120). Twenty patients (28.9%) underwent colonic imaging. Colorectal polyps were found in 40% (8/20) and carcinomas in 20% (4/20). Colonic investigation was performed in five patients (5 of 7) with duodenal adenomas in whom colorectal polyps were found in 40% (2/5) and carcinoma in 20% (1/5), suggesting no increased risk compared with other SDPs. Conclusion: SDPs are largely benign and should not be removed unless symptomatic or adenomatous. Endoscopic removal is safe but there is a high rate of residual and recurrence at second-look endoscopy. Biopsy should be performed to identify large adenomas or carcinomas. The prevalence of colorectal neoplasia did not differ between the group with duodenal adenomas and those with other duodenal lesions. The high rate of colorectal neoplasia may be explained by the age of the population and indication for original procedure. As SDP are reported infrequently a larger study may have the power to test such an association and define the role for colonoscopy in such patients; the BSG website may provide a method for investigating this.